Obesity in Schizophrenia receiving outpatient treatment in regional hospital in Malaysia - A.Talib, Norlelawati; Abdullah, Kartini; Musa, Ramli; Kuzaifah, Norsidah; Wan Sulaiman, Wan Azizi; Abdul Razak, Tariq (2012)
Obesity is an issue of concern among schizophrenia, since obesity is a co-morbid condition that is closely related to metabolic syndrome phenomenon. There are also concerns on the use of atypical anti-psychotic for inducement of obesity. Objective: This present study was done to assess the distribution of body mass index (BMI), antipsychotic used and the prevalence of obesity among schizophrenia patients receiving outpatient treatment at the Tengku Ampuan Afzan Hospital (HTAA), a regional hospital in East-Cost of Malaysia. Method: A total of 216 participants were recruited from the cross sectional study conducted from December, 2010 until April, 2011. Body weight and height of each subject were measured using the standard method. Social demographic and treatment variables were gathered through interview or patient’s clinical record and analyzed using SPSS Software Version 17. Results: The overall BMI mean was 27.14±6.36 kg/m2. There were significant difference in mean BMI between male and female subjects (26.18±5.74 versus (vs.) 28.90±7.06, p=0.02) and between the Malay, Chinese and Indian (27.35±6.58 vs. 25.45±4.17 vs. 30.00±8.67, p=0.041). Obesity (BMI>30kg/m2) and overweight (BMI 25-29.9 kg/m2) subjects were 27.8% (n=60) and 31.9 %( n=69) of the study population respectively. There was significant difference in BMI between the population studied and the healthy Malaysian Adult Nutrition Survey stratified by race, sex and age. BMI distribution was also related with the used of anti-psychotic (p=0.042). Conclusion: Prevalence of obesity among the schizophrenia was greater than in the general healthy population and affects all the three common races of concern. Iatrogenic pharmacotherapy as the factor the occurrence was further supported by this study.